Komunikasi Antarpribadi Orang Tua-Anak Dalam Mengurangi Prilaku Seksual Sebelum Menikah Pada Remaja Hindu - Yasa, I Nyoman Miyarta; Dewi, Ni Putu Sinta (Jurnal Ilmu Sosial dan Humaniora, 2024)
College student who are late teens aged 18-19 years, have sexual development and phases that make them inclined to enter into a heterosexual relationship or relationship such as dating. During this period of dating they have a tendency to engage in sexual behavior, this is a negative thing in Hinduism which prohibits interpersonal communication. Interpersonal communication has the potential to carry out an instrumental function as a tool to influence or persuade others. Parent-adolescent interpersonal communication is a form of parenting process that has an important influence on the formation of adolescents' attitudes regarding sexual relations before marriage. So in this study it is hypothesized that stronger and closer parent-child interpersonal communication can reduce sexual behavior before marriage among Hindu teenagers. This research aims to find the influence of interpersonal communication on sexual behavior before marriage in Hindu teenagers. Quantitative methods were used in this research, collecting data by distributing questionnaires to 53 Hindu teenagers at Bumigora University. The results of this study state that interpersonal communication has a significant negative effect on the attitudes of Hindu teenagers in having sexual relations before marriage. This means that the better the interpersonal communication between Hindu teenagers and their parents, the lower their sexual behavior before marriage.